Phase Separation-Induced Hierarchical Porous PVDF/PMIA Blended Separator with High Wettability and Thermal Stability for Lithium-Ion Batteries. Issue 4 (6th April 2021) - Li, Yinhui; Lin, Quanfan; Chen, Zan; Yuan, Biao; Duan, Cuijia; Yan, Shuo; Shi, Yake
Abstract : Lithium-ion batteries (LIBs) are extensively applied in new energy vehicles and electronic products. The separators directly affect the electrochemical performances and safety of LIBs. However, the wettability and thermal stability of the separators are still an obstacle. In this work, polyvinylidene fluoride (PVDF) with a high wettability and poly(m-phenylene isophthalamide) (PMIA) with a high thermal stability were used to fabricate PVDF/PMIA blended separators with hierarchical porous structures by traditional non-solvent-induced phase separation. The hierarchical porous structure had a favorable effect on the absorption and retention of a carbonate-type electrolyte. Moreover, compared with commercial Polypropylene (PP) and pure PMIA separators, the PVDF/PMIA (1:10, w:w) blended separators exhibited better wettability (the contact angle to the electrolyte was 21°), higher thermal stability (the thermal shrinkage was 3.2% at 250 °C), and higher ionic conductivity (0.75 ms cm −1 ). Additionally, a button cell assembled using the PVDF/PMIA blended separator exhibited the best cycle capability (93.2%) and rate capability (97.9%). Consequently, the PVDF/PMIA blended separators may be promising for application in lithium-ion batteries in the future.